THE EFFECT OF THE INDIAN OCEAN DIPOLE PHENOMENON AND THE CATCHING OF LONG-JAWED MACKEREL (RASTRELIGGER SPP) IN LAMPUNG WATERS - Pamungkas S.; Parmanto (Russian Journal of Agricultural and Socio-Economic Sciences, 2022)
The Indian Ocean Dipole (IOD) is a symptom of climate aberrations caused by the interaction of the ocean and the atmosphere in the Indian Ocean. IOD can influence oceanographic parameters and the density of chlorophyll-a in the waters, affecting fish catches. In Indonesia, the waters that IOD strongly influences are the waters of Lampung, West Sumatra. Therefore, this study analyzed the effect of IOD, oceanographic parameters (sea surface temperature, sea surface salinity, and sea surface currents), and chlorophyll-a density on the catch of long-jawed mackerel (Rastreligger spp) in Lampung waters. The study took place from April 2018 to October 2018 using satellite image data and direct data retrieval at the specified coordinates. The results showed that IOD, oceanographic parameters, and chlorophyll-a density together influenced 58.2% of Rastreligger spp catches in Lampung waters at a 99% significance level, while the rest 41.8% was influenced by other variables outside the model. In other words, a positive IOD phenomenon can increase the catch of Rastreligger spp, while a negative IOD phenomenon will decrease the catch of Rastreligger spp in Lampung waters.